Report on proposed new interior design of Ancasa Express Hotel @Georgetown for Uda Ancasa Sdn. Bhd. at Lot 1238, Jalan Kampung Kolam, 10200 Georgetown, Pulau Pinang / Amyrah Anuar - Anuar, Amyrah (Faculty of Architecture, Planning and Surveying, 2010)
Through studies and reviews covering all aspects of design, a design will be carried out successfully. Research mest be examined from various aspects of external and internal as the diploma in interior architecture projects a key in which student emphasized the understanding of all aspects of the students who had studies interior architecture from the beginning up to the proposed design. The project has been selected for the final project is proposed new interior design of AnCasa Express Hotel @Georgetown. This project aimed to design a more functional space to meet client requirements for the convenience of their customers. Each of the proposed design based on the concept and themes that are applied at the hotel can be attraction to client who came to the hotel. The new interior design is espected for it to raise the standard of corporate image of this hotel. Some research has been conducted for this project. The study that was conducted was a prospective study of the project undertaken, site selection, review of selected buildings and research on environment. It is because to get a design to suit the corporate image of AnCasa Express Hotel @Georgetown. So, i tried my best to design a AnCasa Express Hotel @Georgetown with interesting ideas.